RETROSPECTIVE ANALYSIS OF ALPHA GLOBIN COPY NUMBER VARIATIONS DETERMINED BY MLPA IN THE TRAKYA REGION - Selma Demir; Hakan Gürkan; Damla Eker; Sinem Yalçıntepe; Emine İkbal Atlı; Engin Atlı (İstanbul Tıp Fakültesi Dergisi)
Objective: Alpha thalassemia is a common type of hemoglobinopathy that occurs as a result of deletions or point mutations in the alpha globin gene cluster. The molecular analysis of alpha thalassemia is challenging due to the presence of genes with high sequence similarities in alpha globin gene clusters and pseudogenes. As well as in all genetic diseases, determining the causative mutation types of alpha thalassemia and their frequencies have critical importance for accurate genetic screening and prevention strategies. Material and Method: In our study, alpha globin copy number variations determined by the Multiplex Ligation-dependent Probe Amplifcation (MLPA) method were examined retrospectively with suspicion of alpha thalassemia in 35 female and 43 male patients tested in the Genetic Diseases Diagnosis Center of the Medical Genetics Department at Trakya University Faculty of Medicine. Results: The most common deletion among our patients was the −α3.7 (35.3%), followed by the -α20.5 (10.3%) deletion. The -αSEA deletion was detected in three patients while 4 out of 78 cases were found to have the -αMED deletion. In three patients, a heterozygous large deletion and in one case HS40 regulatory region deletion were detected. In 14 (18%) of the patients, α globin triplications were detected. The -α4.2 deletion was detected in only one of our patients. Conclusion: Our study is the first to report the presence of eight different alpha globin copy number changes and 13 different alpha globin genotypes in the Trakya region.